Hubungan pola asuh demokratis orang tua dengan kedisiplinan anak di Kelompo Bermain - Sunarsih, Sri (STAI Syekh Jangkung, 2025)
Abstract This research aims to determine the relationship between democratic parenting styles and parental education level with the discipline of family KB. Mutiara Cendana Tanjungsekar. This type of research is quantitative research with a correlation research design. The instruments used in this research were observation, scale and questionnaire. The data analysis technique used is descriptive analysis for data presentation, as well as correlation for hypothesis testing. The research results show that there is a relationship between the wrong parenting model causing a lack of student discipline. This is proven in the results of the hypothesis test which shows that there is a significant relationship with a calculated r value of 0.270 and r table of 0.266, so it can be concluded that Ha is accepted and Ho is rejected. Because rcount > rtable. Thus it can be concluded that there is a correlation between parents' level of education and children's discipline. Keywords: parenting style, education level, discipline